(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The Kashmir valley has been endowed with many beautiful and mesmerising natural resources particularly lush green forests, perennial rivers, wetlands, lakes, fertile soils, vast areas of land rich in vegetation cover. Its vast area, diverse vegetation cover, varied flowers, captivating topography, invigorating climate are best suited for the development of apiculture. Generally, there are three types of beekeepers in the Kashmir valley as commercial beekeeper, sideliner Beekeeper and Hobbyist Beekeeper. The commercial beekeeping is the most common beekeeper in the Kashmir valley. Kashmir Valley is emerging as one of the most promising regions in India for commercial beekeeping and honey production. Apiculture offers ample job opportunity for the people of Kashmir valley. The Kashmir valley has an immense potential for beekeeping however it has not been fully utilized due lack of awareness and education about importance of beekeeping. One of the important advantage of beekeeping in Kashmir valley is that it is cheap as it involves low start-up costs. Bees are integral to the preservation of ecological balance and biodiversity in nature. They help in pollination and contribute to genetic and biotic diversity. The Kashmir valley despite having its inherent advantages, imports honey from other states of the country. The department of agriculture is aiming to get geographical indication (GI) tag for “Kashmir Honey” due to its uniqueness in various qualities.